AB0039 Reduction of TH17+ lymphocytes in part of sapho patients on treatment with secukinumab. (15th June 2017) - Assmann, G; Tajali, A; Bamberger, S; Pfreundschuh, M; Schormann, C; Neumann, F
Abstract : Background: The SAPHO syndrome has to be considered as a rare subtype of the disease entity of the seronegative spondylarthritis. The characteristic defining symptoms are synovitis, acne, palmoplantar pustulosis (PPP), and hyperostosis with osteitis. In general, most of SAPHO patients complete the diagnostic criteria for spondylarthritis and/or psoriatic arthritis. The etiology of SAPHO syndrome remains unclear so far, autoimmune dysregulations potentially triggered by bacterial infection with propionibacterium acnes has been discussed. Firinu D et. al (Ref.) has previously published data of higher Th17+ lymphocytes in the periphereal blood in SAPHO patients compared with psoriatic arthritis patients or healthy controls. Activation of the TH17 pathway leads to pro-inflammatory effects mediated by interleukin 17 with stimulation of osteoblast, macrophages, and fibroblasts with the consequences of secretion f pro-inflammatory cytokines such as interleukin 6 and 1, TNF alpha, and MMPs. The interleukin 17 blocking agent secukinumab has been introduced in the armentarium of antirheumatic drugs against seronegative spondylarthritis including psoriatic arthritis. Objectives: To evaluate the count of Th17+ lymphocytes in patients with SAPHO syndrome and psoriatic arthritis before and under treatment with secukinumab. Methods: Periphereal blood was derived from 4 patients with SAPHO syndrome and 4 patients with psoriatic arthritis, respectively before and under 12 week treatment with secukinumab 300mg (dosage: 4 times weekly, then monthly). All patients had received at least one conventional DMARDs and one TNF blocking agent in their medical history. All patients showed active disease with elevated scores of DAS28 and/or HAQ, for SAPHO patients the activity scores of osteitis (from 0 to 6) and PPP (0–6) were estimated by physician. The blood specimen were separated in EDTA containing tubes to separate lymphocytes, which were measured using FACS analysis to evaluate the fraction of Th 17+/CD4+ lymphocytes. The Ethics Committee of Saarland has proven the study, all patients gave their consent to take part in the study. Results: The Th17+lymphocytes were not detectable in 4 patients with psoriatic arthritis and 2 of 4 SAPHO patients before and under 12 week treatment with secukinumab. In 2 of 4 SAPHO patients the fractions of Th17+ lymphocytes were prominent prior to secukinumab application; after treatment duration of 12 weeks one of both developed a depletion of Th17+ cells (figure), the other SAPHO patient a Th17+ cell reduction. Only the two SAPHO patients with diminishing Th17+ lymphocytes have developed treatment response evaluated by reduction of HAQ score (from 1.75 to 1.25), osteitis score (4.5 to 3.0), and PPP score (5.0 to 4.0). Three of 4 psoriatic arthritis patients showed reduced diseases activity under treatment with secukinumab (DAS28 score from 4.22 to 3.45, HAQ 2.25 to 1.5). Conclusions: The measurement of Th17+lymphocytes in the periphereal blood of SAPHO patients could be suggested for further evaluation as possible predictor of treatment response by secukinumab. References: Firinu D, Barca MP, Lorrai MM, Perra S, Cabras S, Muggianu E, Di Martino ML, Manconi PE, Del Giacco SR. TH17 cells are increased in the peripheral blood of patients with SAPHO syndrome. Autoimmunity. 2014 Sep;47(6):389–94. doi: 10.3109/08916934.2014.906582. Epub 2014 Apr 10. Disclosure of Interest: None declared